Effect of caponisation on physicochemical and sensory characteristics of chickens. (7th January 2016) - Amorim, A.; Rodrigues, S.; Pereira, E.; Valentim, R.; Teixeira, A.
Abstract : The meat fats content associated to nutritional and sensory characteristics are the most important concerns of consumers. To study the effect of caponisation on the meat quality of two different breed chickens, slaughtered at 18 weeks of age, raised under the same conditions, the physicochemical and sensory characteristics of capons (castrated males at 8 weeks of age) and roosters' meat of native Amarela Portuguesa and native Pedrês Portuguesa breeds were evaluated. Forty Amarela (20 roosters and 20 capons), 40 Pedrês (20 roosters and 20 capons) chickens, and also, six free-range chicken and six broilers were evaluated. The pH, water-holding capacity, Warner-Bratzler shear force, moisture content, ash, myoglobin, collagen, CP, total fat and fatty acids profile were evaluated in breast and leg meat, according to standard procedures. Leg meat capon showed greater intramuscular fat content ( P ⩽0.05), monounsaturated fatty acids (MUFA) and CP ( P ⩽0.001) than leg roosters. Caponisation increased the content of myoglobin and MUFA ( P ⩽0.05) and reduced the moisture content in the leg ( P ⩽0.05). The main fatty acids found were oleic acid (C18:1), palmitic acid (C16:0) and linoleic acid (C18:2). The greatest value of C18:1 was observed in capon's breast ( P ⩽0.01). Sensory analysis was made to compare the Amarela and Pedrês meat with a free-range chicken and a broiler. The sensory taste panel classified the capon's meat ( Amarela and Pedrês ) as juicier, less fibrous and tougher than rooster's meat. The broiler was in general juicier, tenderer and less fibrous than the other birds. The results of sensory analysis complement those obtained in physicochemical analysis, suggesting that caponisation promotes an overall improvement in meat quality.